2018
DOI: 10.1021/acs.est.8b02348
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of PFOA at the Air–Water Interface during Transport in Unsaturated Porous Media

Abstract: Miscible-displacement experiments are conducted with perfluorooctanoic acid (PFOA) to determine the contribution of adsorption at the air-water interface to retention during transport in water-unsaturated porous media. Column experiments were conducted with two sands of different diameter at different PFOA input concentrations, water saturations, and pore-water velocities to evaluate the impact of system variables on retardation. The breakthrough curves for unsaturated conditions exhibited greater retardation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
184
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(215 citation statements)
references
References 64 publications
(147 reference statements)
13
184
0
Order By: Relevance
“…This is illustrated in Figure S1, which presents the full range of K i values determined for three selected PFAS. These values were determined using the best-fit of the Szyszkowski equation (see below) to the measured surface-tension data sets, with K i values calculated using local slopes for each discrete C. It is relevant to note that the results of recent studies have demonstrated that K i values determined from surface-tension data in this manner are consistent with values determined from miscible-displacement transport experiments for PFOA (Lyu et al, 2018) and PFOS (Brusseau et al, 2019).…”
Section: Determining Fluid-fluid Interfacial Adsorption Coefficientsmentioning
confidence: 93%
See 3 more Smart Citations
“…This is illustrated in Figure S1, which presents the full range of K i values determined for three selected PFAS. These values were determined using the best-fit of the Szyszkowski equation (see below) to the measured surface-tension data sets, with K i values calculated using local slopes for each discrete C. It is relevant to note that the results of recent studies have demonstrated that K i values determined from surface-tension data in this manner are consistent with values determined from miscible-displacement transport experiments for PFOA (Lyu et al, 2018) and PFOS (Brusseau et al, 2019).…”
Section: Determining Fluid-fluid Interfacial Adsorption Coefficientsmentioning
confidence: 93%
“…Measured surface-tension data for the homologous Na-perfluorocarboxylate series. Data reproduced from Lunkenheimer et al (2015) and Tamaki et al (1989), except for C8-UAZ, which is from Lyu et al (2018). QSPR model for log K i versus molar volume for all data.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of phosphorus as a nutrient in agricultural systems, further studies on the effect of phosphorus speciation and concentration on sorption of additional PFAS are warranted. Lastly, other sorption mechanisms unique to PFAS as surfactants include the potential for enhanced retention at the air-water interface in the vadose zone [73,74] (the unsaturated zone of soil above the water table including the root zone).…”
Section: Pfas Sorption and Mobility Characteristicsmentioning
confidence: 99%